Updating the Linnaean Heritage: Names as Tools for Thinking about Animals and Plants (cover) - Minelli, Alessandro; Bonato, Lucio; Fusco, Giuseppe (Zootaxa, 2008)
In December 2007, Zootaxa celebrated the tercentenary of the birth of Linnaeus with an important collection of 30 articles published as volume 1668 under the title Linnaeus Tercentenary: Progress in Invertebrate Taxonomy.